2023
DOI: 10.3390/su151713183
|View full text |Cite
|
Sign up to set email alerts
|

A Choice Experiment Model for Sustainable Consumer Goods: A Systematic Literature Review and Workflow Design

Maria Elena Saija,
Sara Daniotti,
Diego Bosco
et al.

Abstract: Although various methodological biases have been shown, the choice experiment (CE) literature has confirmed the relevance of sustainability in consumers’ purchase choices. Analysing 186 case studies through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, this study defines the state-of-the-art and future perspectives of the CE approach, allowing us—for the first time—to evaluate in a single study all variables to be considered for setting up the CE questionnaire, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…However, to minimize potential bias and ensure a manageable number of choices for the participants, the levels were further reduced to 13. Indeed, previous studies have shown how the number of attributes and levels must be broad enough to describe the product adequately but not be excessively complex enough to overwhelm the customer, resulting in attention bias [17]. The 13 levels selected were distributed as follows: 3 levels for yield, 3 for yield under water stress conditions, 3 for disease resistance, and 4 for price (Table 1).…”
Section: Definition Of Attributes and Levelsmentioning
confidence: 99%
“…However, to minimize potential bias and ensure a manageable number of choices for the participants, the levels were further reduced to 13. Indeed, previous studies have shown how the number of attributes and levels must be broad enough to describe the product adequately but not be excessively complex enough to overwhelm the customer, resulting in attention bias [17]. The 13 levels selected were distributed as follows: 3 levels for yield, 3 for yield under water stress conditions, 3 for disease resistance, and 4 for price (Table 1).…”
Section: Definition Of Attributes and Levelsmentioning
confidence: 99%